A new history of war reporting - Williams, Kevin 1955-
"This book takes a fresh look at the history of war reporting to understand how new technology, new ways of waging war and new media conditions are changing the role and work of today's war correspondent. The focus of this book is on the mechanics of war reporting, the logistical and institutional pressures on correspondents, as well as the role of war propaganda, accreditation and news management in shaping the evolution of the specialism. Previously neglected conflicts and correspondents are reclaimed, and wars considered as key moments in the history of war reporting such as the Crimean War (1854-56) and the Great War (1914-18) are re-evaluated. The use of objectivity as the yardstick by which to assess the performance of war correspondents is questioned. Rather, the emphasis is on war as a messy business which confronts reporters and photographers with conditions that challenge the norms of professional practice. References to the 'demise of the war correspondent' have accompanied the growth of the specialism since the days of the William Howard Russell, the so-called father of war reporting. This highlights the fragile nature of this sub-genre of journalism and emphasises that continuity as much as change characterises the work of the war correspondent. A thematically organised, historically rich introduction, this book is ideal for students of journalism, media and communication"--Provided by publisher.
NM Glova (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: War -- Press coverage; War correspondents